2021
DOI: 10.1038/s41380-021-01364-y
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2 receptors modulate the cholinergic pause and inhibitory learning

Abstract: Cholinergic interneurons (CINs) in the striatum respond to salient stimuli with a multiphasic response, including a pause, in neuronal activity. Slice physiology experiments have shown the importance of dopamine D2 receptors (D2Rs) in regulating CIN pausing yet the behavioral significance of the CIN pause and its regulation by dopamine in vivo is still unclear. Here, we show that D2R upregulation in CINs of the nucleus accumbens (NAc) lengthens the pause in CIN activity ex vi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 76 publications
2
31
0
Order By: Relevance
“…This finding is consistent with recent inhibition studies in which CIN inhibition in the NAc during Pavlovian to Instrumental Transfer (PIT) enhanced the ability of the pavlovian cue to invigorate behavior (Collins et al, 2019). Note, however, that mice with selective Drd2 ablation do not show a deficit in PIT suggesting a more subtle deficit affecting latencies rather than the level of responding (Gallo et al, 2021).…”
Section: Cue Induced Changes In Striatal Da and Ach Levels Are Time Locked And Develop In Parallel With Learningsupporting
confidence: 91%
See 3 more Smart Citations
“…This finding is consistent with recent inhibition studies in which CIN inhibition in the NAc during Pavlovian to Instrumental Transfer (PIT) enhanced the ability of the pavlovian cue to invigorate behavior (Collins et al, 2019). Note, however, that mice with selective Drd2 ablation do not show a deficit in PIT suggesting a more subtle deficit affecting latencies rather than the level of responding (Gallo et al, 2021).…”
Section: Cue Induced Changes In Striatal Da and Ach Levels Are Time Locked And Develop In Parallel With Learningsupporting
confidence: 91%
“…This suggests that even with a shortened dip mice still can learn cue-reward associations. Similarly, we recently described that enhancing the dip lengths by selective overexpression of D2Rs in CINs of the NAc (D2R-OENAcChAT mice) did not affect Pavlovian learning but was associated with a deficit in Go/No-Go learning (Gallo et al, 2021).…”
Section: Implications For Behaviormentioning
confidence: 58%
See 2 more Smart Citations
“…Additionally, loss of D2R in either cell population neither altered basal nor amphetamine-induced locomotor activity. Importantly, the GABA-D2R-cKO mice also likely exhibit loss of D2 receptors from cholinergic interneurons in the striatum and nucleus accumbens (Magno et al, 2017 ), and loss of those receptors may contribute to the observed phenotypes given the roles for D2R regulation of striatal cholinergic functions (Gallo et al, 2021 ; Simpson et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%